Juvenile Fish Composition and Their Growth Aspects on the East Coast of Banyuwangi, East Java, Indonesia - Nazal, Muhammad Faris; Simanjuntak, Charles P.H.; Lumban-Gaol, Jonson; Kurniawan, Fery; Cheung, William W.L.; Reygondeau, Gabriel; Teh, Lydia; Suhita, Ni Putu Asri Ratna (Bogor Agricultural University, Indonesia, 2025)
The east coast of Banyuwangi, Bali Strait, has the potential to function as a nursery area for juvenile fish. Therefore, it is essential to research the ecology of juvenile fish resources. This study aimed to uncover the composition of juvenile fishes and their growth aspects through length-weight relationships and condition factors. We collected 9748 fish specimens from floating lift nets during April, September, December 2023, and February 2024. Identification and morphometric analysis were conducted to calculate fish juvenile assemblage composition, growth patterns from length-weight relationships, and condition factors. The study found 48 species from 26 families and 17 orders. The small pelagic fish group was the most common, including species from the Carangidae, Dorosomatidae, Spratelloididae, Engraulidae, Atherinidae, and Scombridae families in terms of the number of individuals and overall biomass. The fish growth on the east coast of Banyuwangi is optimal, with most fish species exhibiting positive allometric and isometric growth patterns. The overall condition factor of the juvenile fish is above 1.00, indicating that the health of fish resources is good. This suggests that the east coast of Banyuwangi, Bali Strait, can support the growth of fish juveniles and maintain the sustainability of fish resources.